2004
DOI: 10.1042/cs20030374
|View full text |Cite
|
Sign up to set email alerts
|

Low melatonin excretion during mechanical ventilation in the intensive care unit

Abstract: Biochemical markers for the circadian rhythm were studied in patients treated at the ICU (intensive care unit) of two regional hospitals. A normal rhythm is characterized by a relatively higher melatonin and a lower cortisol excretion at night. Disturbances affect sleep, mood and cognitive performance. All urine excreted between 07:00 and 22:00 hours (day) and between 22:00 and 07:00 hours (night) was collected and sampled throughout the entire ICU period (median, 10 days) in 16 patients for the excretion of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 26 publications
2
55
2
9
Order By: Relevance
“…Compared to normal urinary 6-SMT levels our cohort demonstrated an abnormally high secretion of None noted a Propofol causes an initial decrease in melatonin levels from administration for up to 3 h after discontinuation of medication, followed by a possible increase in levels approximately 20 h later [20] 6-SMT in all time periods, even when taking night into account, when both our patients and normal patients consistently had their eyes closed. One previous study did evaluate circadian rhythm measuring urinary 6-SMT levels concurrently with light levels in patients with respiratory failure, but did not relate these levels to light intensity [34]. 6-SMT levels in that study were low in relation to ours, but also demonstrated loss of diurnal rhythm.…”
Section: Discussionmentioning
confidence: 72%
“…Compared to normal urinary 6-SMT levels our cohort demonstrated an abnormally high secretion of None noted a Propofol causes an initial decrease in melatonin levels from administration for up to 3 h after discontinuation of medication, followed by a possible increase in levels approximately 20 h later [20] 6-SMT in all time periods, even when taking night into account, when both our patients and normal patients consistently had their eyes closed. One previous study did evaluate circadian rhythm measuring urinary 6-SMT levels concurrently with light levels in patients with respiratory failure, but did not relate these levels to light intensity [34]. 6-SMT levels in that study were low in relation to ours, but also demonstrated loss of diurnal rhythm.…”
Section: Discussionmentioning
confidence: 72%
“…Little evidence exists to justify these requirements. Prior studies evaluating light levels and outcomes of the critically ill have been limited methodologically [5,8,10] or did not report quantitative ambient light measurements. Outside the ICU, the evidence supporting light as a supplemental therapeutic measure consists of small studies in which light reduced depression in patients with seasonal affective disorder [53][54][55] and decreased agitation and increased orientation in elderly populations of patients with dementia [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…These studies did not quantitatively measure light levels [5] or assess intermediate outcomes such as analgesic use [6][7][8][9]. A single, small (n = 11) unblinded, randomized, interventional study evaluated 2 different light exposures in patients with postoperative esophageal cancer [10] and demonstrated a lower incidence of delirium in the group exposed to more intense light levels.…”
Section: Introductionmentioning
confidence: 98%
“…Erste wissenschaftliche Arbeiten zeigen, dass der zirkadiane Rhythmus der Melatoninsekretion bei kritisch kranken Patienten gestört bzw. teilweise vollständig aufgehoben ist [21,51,54,73] [32,56]. Diese Berichte über Schlafstörungen nach Herzchirurgie wurden durch erneute Untersuchungen in den 1990er-Jahren bestätigt [15].…”
Section: Melatoninunclassified